Quantifying the human wellbeing of the national wetland park: gross ecosystem product accounting of Shandong Mata Lake National Wetland Park - Liu, Jian; Xu, Meng; Wang, Ailing; Sun, Tianxu; Zhang, Chuntao; Chen, Xue; Zhang, Peng (Frontiers in Environmental Science, 2025)
National wetland parks, characterized by robust ecological functions, distinctive natural landscapes, and abundant cultural resources significantly enhance human wellbeing, serve as crucial providers of ecosystem products, and exert substantial influence on local socioeconomic development and ecological conservation. There is an urgent need to carry out the Gross Ecosystem Product (GEP) accounting and monetize the value of ecosystem products. Taking the Shandong Mata Lake National Wetland Park (SMTNWP) in China as the example, and considering the characteristics of wetland parks, this research constructed the GEP accounting index system comprising 11 secondary subjects from the perspectives of regulation and socio-cultural functions. Taking the year 2021 as the research period, the monetary value was assessed based on biophysical value accounting, and the GEP level was determined. The results showed that the GEP of SMTNWP in 2021 is CNY 74.8317 million, with a unit area GEP of 73,200 CNY/hm2. Regulating ecosystem products constitute the core component of GEP, facilitating the sustainable development of wetland conservation and restoration, as well as eco-cultural tourism. Moving forward, efforts in wetland protection, restoration and maintenance should be sustained, and the platforms for promotion, education and scientific research should be proactively established. The research results can offer support and references for the establishment of unified accounting subjects and systems for similar ecosystems and national wetland parks, and translate the human wellbeing of national wetland parks into visual monetization, providing theoretical basis for the government to realize the value of ecosystem products, and further promoting the conversion of ecological value into economic benefits.